Rh(III)-Catalyzed Double Annulation of 3-Phenyl-1,2,4-oxadiazoles with 2-Diazo-1,3-diketones: Access to Pyran-Fused Isoquinolines - Enshen Zhang; Mei Sun; Lvlv Gao (Molecules)
Efficient access to pyranoisoquinoline derivatives via rhodium-catalyzed double C-H functionalization of phenyl oxadiazoles and diazo compounds has been developed. Two C-C bonds and one C-O and C-N bond formation was realized by this tandem reaction, along with the formation of two heterocycles, affording diversified pyran-fused isoquinolines in moderate to good yields with broad functional group tolerance under mild reaction conditions.